Variational Iteration Decomposition Method for Solving Eighth-Order Boundary Value Problems - Muhammad Aslam Noor; Syed Tauseef Mohyud-Din (Differential Equations and Nonlinear Mechanics)
We implement a relatively new analytical technique, the variational iteration decomposition method (VIDM), for solving the eighth-order boundary value problems. The proposed method is an elegant combination of variational iteration method and decomposition method. The analytical results of the equations have been obtained in terms of convergent series with easily computable components. Numerical work is given to check the efficiency of the method. Comparisons are made to confirm the reliability and accuracy of the technique. The technique can be used as an alternative for solving nonlinear boundary value problems.